The Influence of Service Marketing Mix on Decisions on Selection of Educational Services by Guardians of Vocational High School (SMK) Students in Tangerang - Seger Santoso; Benardi Benardi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
This study aims to determine the effect of Service Marketing Mix on the Decision of Selection of Educational Services by Vocational High School (SMK) Guardians in Tangerang. The population in this study were guardians of Vocational High School (SMK) students in Tangerang Regency, namely guardians of Vocational High School (SMK) 6 Tangerang Regency and Vocational High School (SMK) 12 Tangerang Regency, as well as guardians of Vocational High School (SMK) students in South Tangerang is the guardian of science and technology vocational high school students. Data collection was carried out using an instrument in the form of a questionnaire. This type of research is descriptive quantitative using SPSS 26 software . The research sites are at SMKN 6 Tangerang Regency, SMKN 12 Tangerang Regency and SMK IPTEK South Tangerang. The sample in this study amounted to 100 respondents. The analytical method used is multiple regression analysis and tested the validity and reliability. The results of the study show that simultaneously the Service Marketing Mix attributes, namely: Product, Price, Place, Promotion, People, Process and Physical Evidence have a significant effect on the Decisions of Selection of Educational Services by Guardians of Vocational High Schools (SMK) in Tangerang. Meanwhile, partially Physical Evidence has a significant effect on the decision to select educational services by the guardians of Vocational High School (SMK) students in Tangerang. However, other attributes in the form of Product, Price, Place, Promotion, People, and Process have no significant effect on the Decision of Selection of Educational Services by Vocational High School (SMK) Guardians in Tangerang.